Social capital fosters organisational resilience: Evidence from farmer collectives and farmer producer organisations - Shanmuga Priya, K; Selvam, S; Parimalarangan, R; Murugananthi, D; Jeyaprakash, P; Jona Innisairani, P (Plant Science Today, 2025)
Although resilience has become a critical focus in strengthening agricultural organisations, there is still limited systematic understanding of how social capital drives resilience in farmers collectives and farmer producer organisations (FPOs), especially during crises. This review article investigates the critical role of social capital mechanisms in enhancing organisational resilience, particularly within farmers collectives and FPOs. The study focuses on various dimensions of social capital and their impact on organisational resilience during economic crises such as the COVID-19 pandemic. Based on a systematic literature review analysis using the PRISMA (preferred reporting items for systematic reviews and meta-analyses) framework, the findings indicate that FPOs with strong social capital can effectively mobilize resources, adapt to market disruptions and maintain supply chain operations. The analysis highlights that structural social capital, through networks, enables collective action, cognitive social capital, through shared values and understanding facilitates strategic adaptation and relational social capital, based on trust and reciprocity, strengthens organisational response and internal cohesion. The article also investigates social capital's evolution across the different stages of FPO lifecycle, observing that while social capital is high in early stages, it tends to decline as organisations grow and become more market oriented. The study provides practical recommendations for policymakers and FPO leaders to preserve and enhance social capital, emphasizing the importance of member engagement, shared values and continuous communication. By understanding and leveraging social capital mechanisms, FPOs can build more resilient and sustainable agricultural enterprises that support smallholder farmers' economic and social well-being.